The role of parents in promoting play for hospitalized children: A scope review (Research, Society and Development, 2025)
Introduction: This study is based on a qualitative research project for a professional master's degree, contributing with evidence from the literature. Playing is considered a fundamental occupation in childhood and important for child development. The presence of parents is guaranteed by law in the case of child hospitalization, and parents play an important role in promoting play during hospitalization. Objective: To map the evidence and panorama available regarding the role of parents in promoting play in hospitalized children. Methods: Scoping review, considering research and review articles (PUBMED, CINAHL, BVS, LILACS and WEB of SCIENCE), with thematic content analysis. Results: four studies were included and the content analysis allowed us to identify three major themes: (1) Chronic illness in childhood and its impacts on the daily lives of children and families; (2) Parental suffering and parental participation in care and play; and (3) The health team, care and play. Discussion: Chronic diseases promote several changes and interruptions in the daily lives of children and families, especially mothers, the main caregivers. Play, when promoted by parents and staff, can become a means for children to express their feelings and alleviate their anxieties. Final Considerations: Mothers, as the main caregivers, need support and support to balance roles and occupations when their children are ill.